Consensus and dissension among economic science academics in Mexico - Jorge L. Andere; Jorge Luis Canché Escamilla; Álvaro Cano-Escalante (Economic Thought, 2020)
We report general and consensus results of a survey administered to a defined population of economic science academics in Mexico. Our results include insights on economic opinions, scientific aspects of economics, scientific activities, countries' economic performances and methodological orientation. Our outcomes show areas of consensus which, at least partially, are consistent with findings in previous studies. Comparisons between our results and those of other studies suggest that consensus could be constant over time and that economics academics in Mexico seems to show similar levels of skepticism about the importance of rationality assumption as those in other latitudes.
Keywords: A11; A12; A20; 330; surveys; economic thought; academics; economists; Mexico